Hepatic lipase inactivation decreases atherosclerosis in insulin resistance by reducing LIGHT/Lymphotoxin β-Receptor pathway - Andrés-Blasco, Irene; Vinué, Àngela; Herrero-Cervera, Andrea; Martínez-Hervás, Sergio; Nuñez, Laura; Piqueras, Laura; Ascaso, Juan F.; Sanz, MarÍa Jesús; Burks, Deborah Jane; González-Navarro, Herminia (Thrombosis and Haemostasis, 2016)
Coexistence of insulin resistance (IR) and metabolic syndrome (MetS) increases the risk of cardiovascular disease (CVD). Genetic studies in diabetes have linked Hepatic Lipase (HL) to an enhanced risk of CVD while others indicate a role of HL in inflammatory cells. Thus, we explored the role of HL on atherosclerosis and inflammation in a mouse model of MetS/IR, (apoE-/-Irs2+/- mice) and in patients with MetS and IR. HL-deficiency in apoE-/-Irs2+/- mice reduced atheroma size, plaque vulnerability, leukocyte infiltration and macrophage proliferation. Compared with apoE-/-Irs2+/-HL+/+ mice, MCP1, TNFa and IL6 plasma levels, pro-inflammatory Ly6Chi monocytes and activated(CD69+)-T lymphocytes were also decreased in apoE-/-Irs2+/-HL-/- mice. The LIGHT (Tumour necrosis factor ligand superfamily member 14, TNFSF14)/ Lymphotoxin β-Receptor(LTβ-R) pathway, which is involved in T-cell and macrophage activation, was diminished in plasma and in apoE-/-Irs2+/-HL-/- mouse atheromas. Treatment of apoE-/-Irs2+/-HL-/- mice with LIGHT increased the number of Ly6Chi-monocytes and lesion size. Acutely LIGHT-treated apoE-/- mice displayed enhanced proliferating Ly6Chi-monocytes and increased activation of the mitogen-activated protein kinase p38, suggesting that LIGHT/LTβ-R axis might promote atherogenesis by increasing proinflammatory monocytes and proliferation. Notably, MetS-IR subjects with increased atherosclerosis displayed up-regulation of the LIGHT/LTβ-R axis, enhanced inflammatory monocytes and augmented HL mRNA expression in circulating leukocytes. Thus, HL-deficiency decreases atherosclerosis in MetS/IR states by reducing inflammation and macrophage proliferation which are partly attributed to reduced LIGHT/LTβ-R pathway. These studies identify the LIGHT/LTβ-R axis as a main pathway in atherosclerosis and suggest that its inactivation might ameliorate inflammation and macrophage proliferation associated with atherosclerosis burden in MetS/IR.Supplementary Material to this article is available at www.thrombosis-online.com.
Keywords: Atherosclerosis; inflammation; insulin resistance; hepatic lipase; macrophage